Effect of feeding metabolites and acidifier on growth performance, faecal characteristics and microflora in broiler chickens - Mohd Radzi, Rosyidah; Loh, Tek Chwen; Foo, Hooi Ling; Cheng, Xiang Feng; Bejo, Mohd Hair (Medwell Journals, 2011)
A study was conducted to study the effects of feeding metabolites which produced from L. plantarum and acidifier in the diets of broilers chickens on growth performance, microflora count, digesta and faecal pH, immunoglobulin status and volatile fatty acids. A total of 288 male Cobb randomly assigned to five dietary groups for 42 days, basal diet feed (negative control), basal diet feed+neomycin and oxytetracyline (positive control), basal diet feed+0.1% acidifiers (A), basal diet feed+0.5% metabolite (M), basal diet feed+0.1% acidifiers (A) and 0.5% metabolite (M). Higher final body weight and weight gain, lower daily feed intake and feed conversion ratio were found in metabolites and combination of metabolite and acidifier groups while greater lactic acid bacteria count, low faecal and digesta pH and increase volatile fatty acids were found in 3 treated groups. No significant difference was found for immunoglobulin level.